(12p+14q)and(11p-12q)=

Simple and best practice solution for (12p+14q)and(11p-12q)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12p+14q)and(11p-12q)= equation:


Simplifying
(12p + 14q) * and(11p + -12q) = 0

Reorder the terms for easier multiplication:
adn(12p + 14q)(11p + -12q) = 0

Multiply (12p + 14q) * (11p + -12q)
adn(12p * (11p + -12q) + 14q * (11p + -12q)) = 0
adn((11p * 12p + -12q * 12p) + 14q * (11p + -12q)) = 0

Reorder the terms:
adn((-144pq + 132p2) + 14q * (11p + -12q)) = 0
adn((-144pq + 132p2) + 14q * (11p + -12q)) = 0
adn(-144pq + 132p2 + (11p * 14q + -12q * 14q)) = 0
adn(-144pq + 132p2 + (154pq + -168q2)) = 0

Reorder the terms:
adn(-144pq + 154pq + 132p2 + -168q2) = 0

Combine like terms: -144pq + 154pq = 10pq
adn(10pq + 132p2 + -168q2) = 0
(10pq * adn + 132p2 * adn + -168q2 * adn) = 0
(10adnpq + 132adnp2 + -168adnq2) = 0

Solving
10adnpq + 132adnp2 + -168adnq2 = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '2adn'.
2adn(5pq + 66p2 + -84q2) = 0

Factor a trinomial.
2adn((11p + -12q)(6p + 7q)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'adn' equal to zero and attempt to solve: Simplifying adn = 0 Solving adn = 0 Move all terms containing a to the left, all other terms to the right. Simplifying adn = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(11p + -12q)' equal to zero and attempt to solve: Simplifying 11p + -12q = 0 Solving 11p + -12q = 0 Move all terms containing a to the left, all other terms to the right. Add '-11p' to each side of the equation. 11p + -11p + -12q = 0 + -11p Combine like terms: 11p + -11p = 0 0 + -12q = 0 + -11p -12q = 0 + -11p Remove the zero: -12q = -11p Add '12q' to each side of the equation. -12q + 12q = -11p + 12q Combine like terms: -12q + 12q = 0 0 = -11p + 12q Simplifying 0 = -11p + 12q The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 3

Set the factor '(6p + 7q)' equal to zero and attempt to solve: Simplifying 6p + 7q = 0 Solving 6p + 7q = 0 Move all terms containing a to the left, all other terms to the right. Add '-6p' to each side of the equation. 6p + -6p + 7q = 0 + -6p Combine like terms: 6p + -6p = 0 0 + 7q = 0 + -6p 7q = 0 + -6p Remove the zero: 7q = -6p Add '-7q' to each side of the equation. 7q + -7q = -6p + -7q Combine like terms: 7q + -7q = 0 0 = -6p + -7q Simplifying 0 = -6p + -7q The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 3/4x+5/4=50 | | 8=-11+y | | (10x-3)= | | 7=-16+r | | 2(1-x)=3(1+2x)+37 | | -20+x=18 | | 3x-4+1=-2x-5+5 | | n-14=23 | | 19+n=30 | | x-4=14x+9 | | 4/7(2c+9)=3/7 | | 8-3x=12+x | | 6(100-x)+3(100-y)=1500 | | 4x-2+x=-2x+2x | | 2/3x+6=-8 | | 3/5(h+10)=9 | | 4(k+3)+5k=75 | | x/12=16/24 | | x^3+x^2+4=0 | | 3/4x-3=18 | | 3/4-3=18 | | f(x)=28x^2+9x-4 | | 2/3(6t+12)=28 | | X+3/2x+6=0.5 | | x^2-3x+n=0 | | -0.1x^2+16x-100=0 | | 13x-3=62 | | 4x^3+5x^2-36x=45 | | x(x-2)+10=10 | | 0.1x^2+16x-100=0 | | 2t+a=19 | | 8x^2-8=6x |

Equations solver categories